Centralna surowicza choroidoretinopatia – charakterystyka obrazu klinicznego i ocena wpływu stanu ogólnego na rokowanie i przebieg schorzenia. Przegląd piśmiennictwa - Siwiec-Prościńska, Joanna; Prościnski, Tomasz; Kocięcki, Jarosław; Pecold, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Central serous choroidoretinopathy (CSCR) – recurrent disorder characterized by the detachment of neurosensory retina and/or detachment of the RPE in the posterior pole, caused by fluid leakage from choroidal vessels, coming through retinal pigment epithelium layer. The aim of the following paper was to create a historic revue of examinations of CSCR and modern description of signs and symptoms of this disease. CSCR may be present in various clinical forms with different prognosis, and therefore also all kind of retina and choroidea lesions were described. The role of hypertension, steroid treatment and stress in course of CSCR was shown in many studies during past years and for that reason the correlation between those factors and the incidence and the course of CSCR, was analysed. It is important to stress, that in contrast to current opinion, steroids can evoke CSCR and intensificate its symptoms and are contraindicated in the treatment of this disease. To addition CSCR is not always a benign disease, and may cause significant impairment of the visual acuity and colour vision, therefore, it should be carefully followed-up.